Analisis Motivasi Mahasiswa dalam Menempuh Kuliah pada Program Studi Manajemen Jenjang Strata-1 Sekolah Tinggi Ilmu Ekonomi Jambi - Prayetno Agustinus Sitanggang; Friska Artaria Sitanggang (Universitas Batanghari, 2021)
The main purpose of this research paper is to analyze the motivation of students in science education at Sekolah Tinggi Ilmu Ekonomi (STIE) Jambi in the odd semester with Academic Year 2020/2021. Survey research method using motivation closed questionnaire is used in this research. The population in this research are Students at the Management Study Program of academic year 2020/2021 in the odd semester, with samples of 100 Respondents. Analysis of research data using descriptive statistical analysis. These conclusion reveals that the extrinsic factor is dominate students motivation in pursuing the Management Study Program at STIE Jambi were 60,47%, while intrinsic factors were 39,53%. It’s the meaning that the extrinsic factors were 20,94% greater than the intrinsic factors.